Trend Kepemimpinan Abad Ke 21 Terhadap Stress Kerja Karyawan: Analisis Bibliometrik Menggunakan Vosviewer Di Google Scholar - Mita Nur Meilani; Adina Khasanah; Arifani Zakiah Aulianti (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to analyze leadership trends in the 21st century in dealing with employee work stress using a bibliometric approach. Several types of leadership such as transformational, fair and empathy-based leadership are recognized as effective strategies in reducing work stress, of course through analysis of relevant literature. This research uses bibliometric methods. Bibliometric data is obtained from academic databases, such as Google Scholar, Publishing or Perish, Scoups, Vosviewer, with keywords appropriate to the research. This analysis was researched based on published literature. Apart from that, the findings of this research contain the importance of developing leadership trends and the needs of employees in dealing with work stress in the digital era. These findings show an increase in interest in digital-based leadership on work stress. The findings of this research can provide in-depth insight regarding the development and focus of current research, provide a deeper foundation for further research, and contribute to understanding how leadership in the digital era is a key aspect in facing the challenges of work stress among employees. This research is expected to provide insight and a comprehensive view of the scientific literature surrounding 21st century leadership on work stress.